Acrylate polymer, ultraviolet curing type adhesive composition and polaroid
By developing an acrylate polymer and ultraviolet curing adhesive composition, the problems of peeling and corrosion of ITO film adhesives are solved, and polarizer production with high durability and flatness are achieved.
Patent Information
- Application Number
- CN202411971442.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-29
AI Technical Summary
The existing adhesives used for ITO films are easy to peel off and lift up, and the acid-containing adhesive will corrode the ITO film after a long period of use, resulting in a decrease in durability.
An acrylate polymer and ultraviolet curing adhesive composition was developed to form a strong viscosity and low shrinkage adhesive by controlling the molecular weight and components of the acrylate polymer, combining low acid content and high antistatic properties, to ensure the long-term durability of the ITO film.
The adhesive composition can maintain high durability under long-term use, prevent corrosion and lifting of the ITO film, and will not cause poor curling of the polarizer.
Smart Images

Figure CN119899310A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an acrylate polymer, an ultraviolet curing adhesive composition and a polarizer, and belongs to the technical field of polarizers. Background Art
[0002] Polarizer is an optical device used to polarize natural light or light of any polarization to a specific direction. The basic structure of the polarizer includes a PVA layer (polyvinyl alcohol layer) in the middle and two protective layers arranged on both sides of the PVA layer, of which the PVA layer plays a polarizing role. However, since PVA is very easy to hydrolyze and is easily affected by the external environment, in order to protect the physical properties of the polarizing film, a layer of optical film with high light transmittance, good water resistance and certain mechanical strength is generally compounded on both sides of the PVA layer for protection, thus forming the original polarizer. According to different usage requirements, a certain thickness of pressure sensitive adhesive (PSA) is coated on one side of the original polarizer, and a release film is compounded to protect the PSA; and a protective film is compounded on the other side to obtain a semi-finished polarizer. The semi-finished polarizer is then stripped and cut into sheets for edge grinding to obtain a finished polarizer.
[0003] Liquid crystal panels used in liquid crystal display devices, etc., usually have polarizers disposed on both sides of a liquid crystal cell through an adhesive layer, and the liquid crystal cell is formed by a pair of transparent substrates and a liquid crystal layer disposed therebetween. Such an adhesive layer is required to have high durability, for example, in a durability test using heating and humidification, etc., which is usually conducted as an environmental acceleration test, it is required that defects such as peeling and warping due to the adhesive layer do not occur.
[0004] It is known that there is a device in which a transparent conductive film such as an indium tin oxide (ITO) film is formed on a transparent substrate constituting a liquid crystal unit of a liquid crystal panel. Compared with the adhesive layer in contact with a transparent substrate such as a glass substrate, the adhesive layer in contact with the transparent conductive film is prone to peeling, warping, etc., and has a tendency to reduce durability. This is because most of the adhesives currently used for ITO films are acid-free adhesives, which have poor adhesion. As the storage time increases, the adhesion is significantly reduced and warping occurs. Generally speaking, if you want to increase the adhesion, most acid-containing adhesives are used. However, acid-containing adhesives are prone to precipitating H as time goes by. + , the precipitated H + It will corrode the ITO film. Therefore, how to improve the performance of adhesives used for ITO films has become a difficult problem that needs to be solved urgently.
[0005] At the same time, in recent years, UV-curable adhesives have been sought after by manufacturers due to their simple operation and fast curing. If the adhesive can be cured by ultraviolet irradiation, the production efficiency of polarizers will be further accelerated. Summary of the invention
[0006] The present invention is to overcome the drawbacks of the prior art and provide an acrylate polymer, a UV-curable adhesive composition and a polarizer. The UV-curable adhesive composition has strong adhesion and low acid content. On the basis of improving the adhesion, H + The ITO film can be kept intact under long-term use, and can maintain high durability even when exposed to a heated environment or after being placed for a long time. The adhesive composition has a low shrinkage rate, and the polarizer with the adhesive layer will not have curling problems.
[0007] The technical solution adopted by the present invention to solve its technical problem is:
[0008] An acrylate polymer, wherein the main structure of the acrylate polymer adopts (meth) alkyl acrylate, and the main chain and side chain of the acrylate polymer do not contain unsaturated bond functional groups; the weight average molecular weight of the acrylate polymer is 100,000 to 300,000.
[0009] The raw materials for preparing the acrylic ester polymer include 50 to 65 parts by weight of (meth) alkyl acrylate, 0.01 to 2 parts by weight of carboxyl-containing monomer, 3 to 12 parts by weight of hydroxyl-containing monomer, 7 to 25 parts by weight of (meth) acrylate containing aromatic ring, and 0.5 to 3 parts by weight of photoinitiator; after the raw materials are mixed, they are polymerized under ultraviolet light to generate the acrylic ester polymer.
[0010] Among the above raw material components:
[0011] The (meth)acrylic acid alkyl ester is linear or branched, and the number of carbon atoms in the alkyl group is 1-18;
[0012] The carboxyl group-containing monomer is selected from any one of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, carboxypentyl acrylate, carboxypentyl methacrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid;
[0013] The hydroxyl-containing monomer is selected from 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl acrylate, 6-hydroxyhexyl methacrylate, 8-hydroxyoctyl acrylate, 8-hydroxyoctyl methacrylate, 8-hydroxyoctyl acrylate, 8-hydroxyoctyl methacrylate, 6-hydroxyhexyl acrylate, 6-hydroxyhexyl methacrylate, 2-hydroxyethylene glycol. Acrylate, 2-hydroxyethylene glycol methacrylate, 2-hydroxypropylene glycol acrylate, 2-hydroxypropylene glycol methacrylate, 10-hydroxydecyl acrylate, 10-hydroxydecyl methacrylate, 12-hydroxylauryl acrylate, 12-hydroxylauryl methacrylate; more preferably any one of 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl acrylate, and 6-hydroxyhexyl methacrylate;
[0014] The (meth)acrylate containing an aromatic ring is selected from benzyl acrylate, benzyl methacrylate, phenyl acrylate, phenyl methacrylate, o-phenylphenol acrylate, methyl o-phenylphenol acrylate, phenoxy acrylate, phenoxy methacrylate, phenoxyethyl acrylate, phenoxyethyl methacrylate, phenoxypropyl acrylate, phenoxypropyl methacrylate, phenoxydiethylene glycol acrylate, phenoxydiethylene glycol methacrylate, ethylene oxide modified nonylphenol acrylate, ethylene oxide modified nonylphenyl Any one of phenol methacrylate, 2-hydroxy-3-phenoxypropyl acrylate, 2-hydroxy-3-phenoxypropyl methacrylate, methoxybenzyl acrylate, methoxybenzyl methacrylate, toluene acrylate, toluene methacrylate, 2-naphthylethyl acrylate, 2-naphthylethyl methacrylate, 2-naphthyloxyethyl acrylate, 2-(4-methoxy-1-naphthyloxy)ethyl acrylate, 2-(4-methoxy-1-naphthyloxy)ethyl methacrylate, biphenyl acrylate, and biphenyl methacrylate;
[0015] The photoinitiator is selected from any one of benzoin diethyl ether, 1-hydroxycyclohexyl phenyl ketone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, 2-methyl-4-methylthio-2-morpholinophenylpropiotone, and 2-hydroxy-2-methyl-1-phenylpropiotone, or a mixture of several thereof.
[0016] The present invention also provides a UV-curable adhesive composition, comprising 20 to 40 parts by weight of the acrylate polymer as described in any one of claims 1 to 3, 15 to 35 parts by weight of an amide group-containing monomer, 13 to 40 parts by weight of an alkyl (meth)acrylate, 5 to 8 parts by weight of a silane compound, 1 to 5 parts by weight of an antistatic agent and 0.4 to 1.0 parts by weight of a photoinitiator.
[0017] Among the above raw material components:
[0018] The amide group-containing monomer refers to a compound containing an amide group in its structure and containing polymerizable unsaturated double bonds such as acryloyl, methacryloyl, and vinyl groups;
[0019] The (meth) alkyl acrylate is a linear or branched alkyl acrylate;
[0020] The silane compound is a reactive silane compound containing silicon atoms;
[0021] The antistatic agent is any one or two of conductive polymers, ionic compounds, conductive particles, organic silicon compounds, and nano-scale carbon nanotubes;
[0022] The photoinitiator is selected to have an absorption wavelength band of 300-400nm for active energy rays.
[0023] More preferably,
[0024] The amide group-containing monomer can be selected from any one of (meth)acrylamide, NN-dimethyl(meth)acrylamide, NN-diethyl(meth)acrylamide, N-isopropylacrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-propyl(meth)acrylamide, aminomethyl(meth)acrylamide, aminoethyl(meth)acrylamide, N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylpyrrolidone, and N-vinyl-ε-caprolactam;
[0025] The carbon number of the alkyl group in the (meth)acrylic acid alkyl ester is 4 to 8;
[0026] The silane compound is selected from any one of 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloxydecyltrimethoxysilane, 10-acryloxydecyltrimethoxysilane, 10-methacryloxydecyltriethoxysilane, and 10-methacryloxydecylethoxysilane;
[0027] The antistatic agent is selected from one or a mixture of two or more conductive polymers such as polyaniline and polythiophene; an appropriate amount of dopant may be added to the conductive polymer;
[0028] The photoinitiator is a compound of OXE01 and 907, and the compounding ratio of the two is 1: (3-5).
[0029] The viscosity η of the UV-curable adhesive composition at 25° C. is in the range of 2000cps≤η≤5000cps; the glass transition temperature Tg of the adhesive composition is -60° C.≤Tg≤-30° C.; and the gel fraction of the adhesive composition is 75% to 85%.
[0030] The present invention also provides a polarizer, comprising a PVA layer, an outer protective layer and an inner protective layer adhered to the upper and lower surfaces of the PVA layer by UV glue, a release film is adhered to the outer side of the inner protective layer by an adhesive layer, and a protective film is arranged on the outer side of the outer protective layer; the adhesive layer is a UV-curable adhesive composition.
[0031] The thickness of the adhesive layer is 10 to 30 μm, and the surface resistance is 9.9×10 11 Ω / □ or less.
[0032] When the inner protective layer is a hydrophilic film material, the water contact angle when it contacts the adhesive composition is ≤35°; when the inner protective layer is a hydrophobic film material, the water contact angle when it contacts the adhesive composition is ≤48°.
[0033] The beneficial effects of the present invention are:
[0034] The present invention specifically develops an acrylate polymer and a UV-curable adhesive composition prepared by using the acrylate polymer, and a polarizer using the UV-curable adhesive composition in view of the characteristics of the ITO film. By designing the adhesive composition, including the molecular weight and component research of the acrylate polymer, the matching selection of the release film material and the initiator type, the matching control of the film material contact angle and the viscosity of the adhesive composition, etc., the adhesive layer and the film material are more firmly combined, the gel fraction is controlled, and the UV curing energy is controlled to obtain a polarizer with good bonding durability with ITO, good appearance flatness, and no warping defects.
[0035] The main framework of the acrylate polymer of the present invention adopts (meth) alkyl acrylate and a certain proportion of carboxyl-containing monomers, hydroxyl-containing monomers, and aromatic ring-containing (meth) acrylates to synthesize an acrylate polymer without unsaturated bonds by ultraviolet curing in the presence of a photoinitiator. The degree of polymerization is relatively large, and the weight-average molecular weight is controlled to be between 100,000 and 300,000. The acrylate polymer is the main molecular structure that plays a bonding role, and the appropriate molecular weight has a great influence on the viscosity and durability of the adhesive. If the molecular weight is too small, the adhesive has no pressure sensitivity and viscosity, and the durability is poor; if the molecular weight is too large, the viscosity of the bonding layer is high, which will limit the amount of the main agent added. Therefore, by controlling the type, amount, and synthesis reaction parameters of the acrylate polymer raw materials, the structure of the polymer is controlled, and the weight-average molecular weight of the acrylate polymer is controlled to be between 100,000 and 300,000. A larger molecular weight can control the precipitation of H + Speed is an important technical feature to ensure the adhesion, durability and coating properties of the adhesive.
[0036] Aromatic groups are also introduced into the acrylate polymer of the present invention. The aromatic ring structure has high stability. The conjugated π electron system makes its energy lower, thereby reducing the possibility of chemical reaction. It has good thermal stability and helps to improve the high temperature durability of the adhesive.
[0037] The UV-curable adhesive composition of the present invention is an adhesive composition obtained by compounding the above-mentioned acrylate polymer with a specific monomer, a silane compound, an antistatic agent, an OXE01 photoinitiator and a 907 photoinitiator. The composition has strong adhesion, low acid content and excellent durability. The adhesion of the composition is improved by introducing an acidic group. However, when applied to a transparent conductive film (layer), especially an ITO thin film conductive film (layer), H is not easily precipitated. + It will not corrode or dissolve the adhesive layer. Therefore, it can maintain high durability and is not easy to warp even when exposed to a heated environment or after being left for a long time.
[0038] The gel fraction of the UV curable adhesive composition after curing is 75% to 85%, and the durability at high temperature 80°C, high temperature and humidity 60°C, 90%RH, cold -35°C, and hot and cold shock -35 to 80°C can reach 1000 hours without peeling, warping, and blistering. The initial peeling force of the ITO glass is 150 to 300 gf / 25mm, and the peeling force slowly increases to 800 to 1200 gf / 25mm at room temperature for 30 days. The viscosity of the adhesive composition at 25°C is greater than or equal to 2000 cps and less than or equal to 5000 cps, which is convenient for coating.
[0039] The glass transition temperature Tg of the adhesive composition of the present invention is greater than or equal to -60°C and less than or equal to -30°C. When Tg is less than -60°C, the adhesive layer is too soft and the cohesive strength is insufficient. When Tg is greater than -30°C, the adhesive layer is too hard and the bonding strength decreases, affecting the use effect and durability of the product.
[0040] The present invention also provides a polarizer using the above-mentioned UV-curable adhesive composition, which has good appearance flatness and no curling. After the adhesive composition is coated, the release film is used as the incident surface by UV irradiation, and the release film material has a transmittance of 75% or more to the active energy ray of 300-400nm, and the intensity of the wavelength UVA is greater than or equal to 100mw / cm 2 , less than or equal to 200mw / cm 2 The total energy of UVA is 2000~3000mj / cm 2 , light curing time is 1-3min, and the thickness of the adhesive layer is 10-30μm.
[0041] During the coating process of the adhesive composition, the water contact angle during coating is controlled differently according to the hydrophilic and hydrophobic properties of the film material in contact with the adhesive composition, thereby ensuring sufficient contact and adhesion between the adhesive and the film material and improving the adhesion performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Schematic diagram of the structure of the polarizer of the present invention;
[0043] In the figure: 1. PVA layer; 2. UV adhesive layer; 3. outer inner protective layer; 4. inner inner protective layer; 5. protective film; 6. UV-curable adhesive layer; 7. release film. DETAILED DESCRIPTION
[0044] The present invention is described in detail below with reference to the accompanying drawings.
[0045] The directions or their approximate terms described throughout the present invention, such as "front", "rear", "left", "right", "up (top)", "down (bottom)", "inside", "outside", "side", etc., are mainly used with reference to the directions of the accompanying drawings. Each direction or its approximate terms are only used to assist in the explanation and understanding of the embodiments of the present invention, and are not used to limit the present invention.
[0046] An acrylate polymer, the main structure of which adopts (meth) alkyl acrylate, contains no unsaturated bond functional groups in the main chain and side chain of the polymer, and the weight average molecular weight of the acrylate polymer is controlled to be 100,000 to 300,000.
[0047] Specifically, in terms of weight percentage, the acrylic ester polymer includes 50 to 65 parts of alkyl (meth)acrylate, 0.01 to 2 parts of carboxyl-containing monomer, 3 to 12 parts of hydroxyl-containing monomer, 7 to 25 parts of aromatic ring-containing (meth)acrylate, and 0.5 to 3 parts of photoinitiator.
[0048] The alkyl (meth)acrylate is preferably linear or branched, and the number of carbon atoms in the alkyl group is 1-18. The alkyl group in the alkyl (meth)acrylate is further preferably selected from methyl, ethyl, propyl, isopropyl, butyl, isobutyl, pentyl, hexyl, cyclohexyl, heptyl, 2-ethylhexyl, isooctyl, nonyl, decyl, isodecyl, undecyl, isotetradecyl, lauryl, tridecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, etc., and the above groups can be used alone or in combination; when multiple alkyl groups are used in combination, the average number of carbon atoms in the alkyl group is preferably 3-12.
[0049] The carboxyl group-containing monomer can be selected from acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, carboxypentyl acrylate, carboxypentyl methacrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. Among the above carboxyl group-containing monomers, acrylic acid is more preferred from the viewpoints of copolymerizability, price and adhesive properties.
[0050] The hydroxyl-containing monomer may be selected from 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl acrylate, 6-hydroxyhexyl methacrylate, 8-hydroxyoctyl acrylate, 8-hydroxyoctyl methacrylate, 8-hydroxyoctyl acrylate, 8-hydroxyoctyl methacrylate, 6-hydroxyhexyl acrylate, 6-hydroxyhexyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxybutyl methacrylate, 2-hydroxyethyl ... Preferably, the present invention is characterized in that the present invention is acrylate, 2-hydroxyethylene glycol methacrylate, 2-hydroxypropylene glycol acrylate, 2-hydroxypropylene glycol methacrylate, 10-hydroxydecyl acrylate, 10-hydroxydecyl methacrylate, 12-hydroxylauryl acrylate, 12-hydroxylauryl methacrylate; more preferably, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl acrylate, 6-hydroxyhexyl methacrylate.
[0051] The (meth)acrylate containing an aromatic ring can meet the durability requirements of the transparent conductive layer. The aromatic ring group can be selected from a benzene ring, a naphthalene ring or a biphenyl ring. The (meth)acrylate containing an aromatic ring is further preferably selected from: benzyl acrylate, benzyl methacrylate, phenyl acrylate, phenyl methacrylate, o-phenylphenol acrylate, methyl o-phenylphenol acrylate, phenoxy acrylate, phenoxy methacrylate, phenoxyethyl acrylate, phenoxyethyl methacrylate, phenoxypropyl acrylate, phenoxypropyl methacrylate, phenoxydiethylene glycol acrylate, phenoxydiethylene glycol methacrylate, ethylene oxide modified nonylphenol acrylate, ethylene oxide Modified nonylphenol methacrylate, 2-hydroxy-3-phenoxypropyl acrylate, 2-hydroxy-3-phenoxypropyl methacrylate, methoxybenzyl acrylate, methoxybenzyl methacrylate, cresyl acrylate, cresyl methacrylate, 2-naphthylethyl acrylate, 2-naphthylethyl methacrylate, 2-naphthyloxyethyl acrylate, 2-(4-methoxy-1-naphthyloxy)ethyl acrylate, 2-(4-methoxy-1-naphthyloxy)ethyl methacrylate, biphenyl acrylate, biphenyl methacrylate.
[0052] The photoinitiator can be selected from one or more mixtures of benzoin diethyl ether, 1-hydroxycyclohexyl phenyl ketone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, 2-methyl-4-methylthio-2-morpholinophenylpropiotone, and 2-hydroxy-2-methyl-1-phenylpropiotone.
[0053] The amount of each component in the acrylic ester polymer (in parts by weight) is:
[0054] The content of the alkyl (meth)acrylate is 50 to 65 parts, preferably 52 to 62 parts. If the content of the alkyl (meth)acrylate is less than 50 parts, the molecular weight of the obtained acrylate polymer is low, the hardness of the acrylate polymer is high, and the flexibility is poor. If the content of the alkyl (meth)acrylate is higher than 65 parts, the molecular weight of the obtained acrylate polymer is too high, the hardness of the acrylate polymer is low, and the flexibility is too large.
[0055] The content of the carboxyl group-containing monomer is 0.01 to 2 parts, preferably 0.05 to 1.5 parts, and more preferably 0.05 to 1 part. If the content of the carboxyl group-containing monomer is less than 0.01 parts, the adhesive viscosity is too low, and there is a tendency to fail to meet the durability requirements; if the content is greater than 2 parts, the acidic carboxyl content is high, and H + This may cause corrosion of the transparent conductive layer and may fail to meet durability requirements.
[0056] The content of the hydroxyl-containing monomer is 3 to 12 parts, preferably 4 to 10 parts. The hydroxyl group can form hydrogen bonds with polar groups on the surface of the adherend, thereby improving the adhesion. If the content of the hydroxyl-containing monomer is less than 3 parts, there is a tendency that the durability and adhesion characteristics cannot be satisfied; and if the content is greater than 12 parts, the hydroxyl group has hydrophilicity and there is a tendency that the high temperature and humidity durability cannot be satisfied.
[0057] The content of the (meth)acrylate containing an aromatic ring is 7 to 25 parts, preferably 7 to 22 parts, and more preferably 7 to 18 parts. The aromatic ring structure has high stability and high molecular chain rigidity. Due to the conjugated π electron system, its energy is lower, thereby reducing the possibility of chemical reactions, having good thermal stability, and helping to improve the high temperature durability of the adhesive. If the content of the (meth)acrylate containing an aromatic ring is less than 7 parts, there is a tendency for the durability to decrease. If the content of the (meth)acrylate containing an aromatic ring is greater than 25 parts, due to the high rigidity of the molecular chain, the adhesive has too high a hardness and a tendency for the durability to decrease. In addition, the (meth)acrylate containing an aromatic ring is expensive and needs to be added in an appropriate amount.
[0058] The weight ratio of the photoinitiator is 0.5 to 3 parts, preferably 1 to 2.0 parts. If the content of the photoinitiator is less than 0.5 parts, the polymerization molecular weight requirement cannot be met, the reaction speed is slow, and the efficiency is low; if the content is greater than 3 parts, it may cause poor controllability of the polymer molecular weight, and the initiator may remain in the polymer, causing instability in the storage of the polymer.
[0059] The preparation method of the acrylic acid ester polymer is:
[0060] The (meth) acrylate alkyl ester, carboxyl-containing monomer, hydroxyl-containing monomer, aromatic ring-containing (meth) acrylate and photoinitiator are mixed, and the acrylate polymer is obtained by irradiating ultraviolet light at a stirring speed of 200 r / min. The ultraviolet light intensity is preferably UVA15-50mw / cm 2 The cumulative energy is preferably UVA 2600~3500mj / cm 2 / 100g.
[0061] A UV curable adhesive composition comprises an acrylate polymer, an amide group-containing monomer, an alkyl (meth)acrylate, a silane compound, an antistatic agent and a photoinitiator.
[0062] The acrylic acid ester polymer is an acrylic acid ester polymer prepared by the above method and having a weight average molecular weight controlled at 100,000 to 300,000, which will not be described in detail here.
[0063] The amide-containing monomer refers to a compound containing an amide group in its structure and containing polymerizable unsaturated double bonds such as acryloyl, methacryloyl, and vinyl, which can improve the durability of the transparent conductive layer. Specifically, it can be selected from: (methyl)acrylamide, NN-dimethyl (methyl)acrylamide, NN-diethyl (methyl)acrylamide, N-isopropyl acrylamide, N-methyl (methyl)acrylamide, N-butyl (methyl)acrylamide, N-hexyl (methyl)acrylamide, N-hydroxymethyl (methyl)acrylamide, N-propyl (methyl)acrylamide, aminomethyl (methyl)acrylamide, aminoethyl (methyl)acrylamide, N-(methyl)acryloylmorpholine, N-(methyl)acryloylpiperidine, N-(methyl)acryloylpyrrolidine, N-vinylpyrrolidone, N-vinyl-ε-caprolactam; preferably, it is a lactam monomer containing N-vinyl.
[0064] The (meth)acrylic acid alkyl ester may be selected from linear or branched alkyl acrylates, wherein the alkyl group has 4 to 8 carbon atoms, preferably 6 to 8 carbon atoms.
[0065] The silane compound is a reactive silane compound containing silicon atoms, which can be selected from: 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloxydecyltrimethoxysilane, 10-acryloxydecyltrimethoxysilane, 10-methacryloxydecyltriethoxysilane, 10-methacryloxydecylethoxysilane.
[0066] The antistatic agent is used as a material for forming the organic conductive layer of the transparent conductive substrate. From the perspective of optical properties, appearance, antistatic effect, and stability of the antistatic effect during heating and humidification, it is preferred to use a conductive polymer; it is further preferred to use one or a mixture of two or more conductive polymers such as polyaniline and polythiophene. According to specific performance requirements, an appropriate amount of dopant can also be added to the conductive polymer, for example: polystyrene sulfonic acid, a high-valent metal compound of a halogen element containing iodine, bromine, and chlorine components, and when the adhesive layer (adhesive composition) contains an epoxy silane coupling agent and an organic conductive polymer (for example, polythiophene) is used, as a dopant, it is preferred to use a component other than the sulfonic acid component. In addition, the antistatic agent can also be selected from ionic compounds, conductive particles, organosilicon compounds, nano-scale carbon nanotubes, etc. Among these, they can be used alone or in combination of two or more.
[0067] The photoinitiator is selected from initiators having an absorption wavelength band of 300-400nm for active energy rays, preferably OXE01+907, and the compounding ratio of the two is 1:(3-5), preferably 1:4.
[0068] Regarding the content of each component in the UV-curable adhesive composition (in parts by weight),
[0069] The content of the acrylic ester polymer is 20 to 40 parts, preferably 25 to 35 parts. If the content of the acrylic ester polymer is less than 20 parts, the durability of the adhesive layer tends to decrease; if the content of the acrylic ester polymer is greater than 40 parts, the adhesive composition has high viscosity and poor applicability.
[0070] The content of the amide group-containing monomer is 15 to 35 parts. If the content of the amide group-containing monomer is less than 15 parts, the durability of the adhesive layer tends to decrease under heating conditions, and if the content of the amide group-containing monomer is greater than 35 parts, the initial adhesion of the adhesive layer tends to decrease.
[0071] The content of the alkyl (meth)acrylate is 13 to 40 parts. If the content is less than 13 parts, the initial adhesion of the adhesive layer tends to decrease; if the content is greater than 40 parts, the adhesion of the adhesive layer tends to increase too fast over time.
[0072] The content of the silane compound is controlled to be 5 to 8 parts. If the content is less than 5 parts, the adhesive layer tends to have a reduced adhesion over time; if the content is greater than 8 parts, the adhesive layer tends to have reduced durability and precipitation.
[0073] The content of the antistatic agent is controlled to be 1 to 5 parts. If the content is less than 1 part, the antistatic effect is poor; if the content is greater than 5 parts, the adhesive layer has a tendency to decrease in durability and precipitation.
[0074] The content of the photoinitiator is preferably controlled at 0.4 to 1.0 parts. When the content of the photoinitiator is less than 0.4 parts, the UV curing reaction is slow and the cohesive strength of the adhesive layer tends to decrease; when the content of the photoinitiator is greater than 1.0 parts, the residual photoinitiator tends to migrate.
[0075] The preparation method of the UV-curable adhesive composition is as follows:
[0076] Acrylate polymer, amide-containing monomer, (meth) alkyl acrylate, silane compound and antistatic agent are weighed in proportion, mixed and stirred evenly; then a photoinitiator is added and stirred until dissolved evenly, and an adhesive glue is obtained after defoaming, which can be directly applied and used.
[0077] It should be noted that: 1. The preparation process and storage environment of the adhesive must be protected from light; 2. The prepared adhesive must be used within 48 hours, otherwise its performance will be affected.
[0078] The adhesive composition prepared by the above method has a viscosity η at 25° C. in the range of 2000 cps≤η≤5000 cps. The glass transition temperature T g :-60℃≤T g ≤-30℃.
[0079] When the adhesive composition prepared by the above method is bonded to the polarizer, the hydrophilic properties of the polarizer vary. When the inner protective layer is a hydrophilic film material, such as a TAC film, the water contact angle when it contacts the adhesive composition is less than or equal to 35°; when the inner protective layer is a hydrophobic film material, such as a PMMA film, a COP film, or a COC film, the water contact angle when it contacts the adhesive composition is less than or equal to 48°.
[0080] A polarizing film, such as Figure 1 As shown, it includes a PVA layer 1, an outer protective layer 3 and an inner protective layer 4 attached to the upper and lower surfaces of the PVA layer 1 through a UV adhesive 2, a release film 7 is adhered to the outer side of the inner protective layer 4 through an adhesive layer 6, and a protective film 5 is arranged on the outer side of the outer protective layer 3. The adhesive layer 6 adopts the ultraviolet curing adhesive of the present invention.
[0081] In the above polarizer, the polarizer adhesive layer is in contact with the release film, and the residual bonding rate of the release film is greater than or equal to 95%. The release film material has a transmittance of 75% or greater to the active energy ray of 300-400nm.
[0082] In the above polarizer, the gel fraction of the adhesive layer is controlled to be 75 to 85%.
[0083] In the above polarizer, the thickness of the adhesive layer is 10 to 30 μm, and the surface resistance is 9.9×10 11 Ω / □ or less.
[0084] For the above-mentioned polarizer with adhesive layer, the outer protective layer is the side opposite to the adhesive layer, and one of TAC, PMMA, and PET films can be selected according to the different functions of the product; the inner protective layer is the side in contact with the adhesive layer, and one of TAC, PMMA, COP, and COC films can be selected; the outer protective layer and the protective film contact surface can also include a functional layer, such as AG, HC, or LR layer. If the wear resistance and hardness of the functional layer are good, the outer side of the functional layer may not need a protective film.
[0085] A method for preparing a polarizer, the method comprising the following steps:
[0086] S1. Unwind the PVA original film at the first unwinding position, and perform swelling, dyeing, bridging, stretching, washing, fixing and drying to obtain PVA polarized film; adhere inner protective layers to the upper and lower surfaces of the PVA polarized film respectively by UV glue, the outer layer is the outer inner protective layer, and the layer coated with PSA glue is the inner inner protective layer;
[0087] As the protective layer, the water contact angle of the TAC film when in contact with the adhesive composition is not greater than 35°, and the water contact angle of the PMMA film, COP film, and COC film when in contact with the adhesive composition is not greater than 46°.
[0088] The contact angle reduction method may adopt an alkali washing method, a corona method or a plasma method according to the film material characteristics, actual processing technology and cost-effectiveness.
[0089] S2, unwinding the release film at the second unwinding station, coating the ultraviolet curing adhesive composition, laminating it to the inner protective layer, and curing it by UV lamp irradiation, where the irradiated surface is the release film surface.
[0090] S3, unwinding the protective film at the third unwinding position, laminating it to the outer inner protective layer, and rewinding it to obtain a polarizer semi-finished product; the protective film lamination can also be performed separately on a separate line.
[0091] S4, the semi-finished polarizer is unwound on the cutting line, and is cut and edge-grinded to obtain a finished polarizer sheet.
[0092] In the method for preparing the polarizer containing the UV-curable adhesive layer, the UV-curable adhesive composition may be coated on the inner protective layer in S2, and then attached to the release surface of the release film.
[0093] In the method for manufacturing a polarizing plate, the intensity of the irradiation wavelength UVA is greater than or equal to 100 mw / cm 2 , less than or equal to 200mw / cm 2 ; The total energy of UVA is 2000~3000mj / cm 2 , light curing time is 1 to 3 minutes.
[0094] In the method for preparing the polarizer containing UV-curable PSA adhesive, the UV lamp irradiation is incident on the release film surface.
[0095] The present invention will be further described below in conjunction with the embodiments.
[0096] In the following examples, except for the manufacturers and brands specified, other raw materials are commercially available products and are chemically pure.
[0097] Example 1
[0098] 1. Preparation of acrylate polymer:
[0099] 50 parts by weight of dodecyl acrylate, 0.5 parts by weight of acrylic acid, 10 parts by weight of 2-hydroxyethyl acrylate, and 25 parts by weight of 2-hydroxy-3-phenoxypropyl methacrylate were stirred until uniform to obtain a mixed solution a;
[0100] Add 0.5 parts by weight of 1-hydroxycyclohexyl phenyl ketone to the mixed solution a, stir and mix evenly, and irradiate with ultraviolet light for polymerization at a stirring speed of 200 r / min to obtain an acrylate polymer. The ultraviolet light intensity is UVA 15mw / cm 2 , cumulative energy UVA 2600mj / cm 2 / 100g.
[0101] After testing, the weight average molecular weight of the obtained acrylate polymer is 200,000.
[0102] 2. Preparation of UV-curable adhesive composition:
[0103] 38 parts by weight of the above-prepared acrylic polymer, 25 parts by weight of NN-dimethyl(meth)acrylamide, 15 parts by weight of isooctyl acrylate, 7 parts by weight of vinyltrimethoxysilane, and 2 parts by weight of an ionic antistatic agent (FC-4400) were stirred evenly, and then 0.17 parts by weight of photoinitiator OXE01 and 0.83 parts by weight of 907 were added, stirred until uniformly dissolved, defoamed, and stored away from light for later use.
[0104] 3. A method for preparing a polarizer, comprising the following steps:
[0105] S1. Unwind the PVA original film at the first unwinding position, and perform swelling, dyeing, bridging, stretching, washing, fixing and drying to obtain PVA polarizers; adhere PMMA and PMMA inner protective layers to the upper and lower surfaces of the PVA polarizers respectively by UV glue, the outer layer is the outer layer, and the PSA adhesive layer is the inner layer.
[0106] The water contact angle of the PMMAinner protective layer in contact with the adhesive layer is 47° after corona treatment.
[0107] S2, unwinding the release film at the second unwinding station, coating the ultraviolet curing adhesive composition, laminating the inner PMMA inner protective layer after S1, and curing it through UV irradiation, with the irradiated surface being the release film surface.
[0108] S3, unwinding the PET protective film at the third unwinding position, attaching it to the outer inner protective layer passing through S2, and rewinding it to obtain a semi-finished polarizer.
[0109] S4, the upper semi-finished polarizer is unwound on the cutting line, and is cut and edge-grinded to obtain a finished polarizer sheet.
[0110] The preparation method of the upper polarizer, wherein the UV curing in S2 uses a high pressure mercury lamp UVA curing energy of 2200mj / cm 2 , UVA light intensity is 110mw / cm 2 , irradiation time 2min.
[0111] Example 2
[0112] 1. Preparation of acrylate polymer:
[0113] 65 parts by weight of butyl acrylate, 2.0 parts by weight of methacrylic acid, 3 parts by weight of 4-hydroxybutyl acrylate, and 15 parts by weight of phenoxypropyl acrylate were stirred until uniform to obtain a mixed solution a;
[0114] Add 2 parts by weight of 1-hydroxycyclohexyl phenyl ketone to the mixed solution a, stir and mix evenly, and irradiate with ultraviolet light for polymerization at a stirring speed of 200 r / min to obtain an acrylate polymer, with an ultraviolet light intensity of UVA 25mw / cm 2 , cumulative energy UVA2600mj / cm 2 / 100g.
[0115] After testing, the weight average molecular weight of the obtained acrylate polymer is 100,000.
[0116] 2. Preparation of UV-curable adhesive composition:
[0117] 20 parts by weight of the above-prepared acrylic polymer, 25 parts by weight of N-vinyl pyrrolidone, 25 parts by weight of isooctyl acrylate, 5 parts by weight of 4-vinylbutyltrimethoxysilane, and 1 part by weight of an ionic antistatic agent (FC-4400) were stirred evenly, and then 0.1 parts by weight of a photoinitiator OXE01 and 0.4 parts by weight of 907 were added, stirred until uniformly dissolved, defoamed, and stored away from light for later use.
[0118] 3. A method for preparing a polarizer, comprising the following steps:
[0119] S1. Unwind the PVA original film at the first unwinding position, and perform swelling, dyeing, bridging, stretching, washing, fixing and drying to obtain PVA polarizers; adhere PET and TAC inner protective layers to the upper and lower surfaces of the PVA polarizers respectively through UV glue, the outer layer is the outer layer, and the PSA adhesive layer is the inner layer.
[0120] The water contact angle of the TAC inner protective layer in contact with the adhesive layer is 33° after alkali washing.
[0121] S2, unwinding the release film at the second unwinding station, coating the ultraviolet curing adhesive composition, laminating the inner TAC inner protective layer after S1, and curing it through UV irradiation, with the irradiated surface being the release film surface.
[0122] S3, unwinding the PET protective film at the third unwinding position, attaching it to the outer inner protective layer passing through S2, and rewinding it to obtain a semi-finished polarizer.
[0123] S4, the upper semi-finished polarizer is unwound on the cutting line, and is cut and edge-grinded to obtain a finished polarizer sheet.
[0124] The preparation method of the upper polarizer, wherein the UV curing in S2 uses a high pressure mercury lamp UVA curing energy of 2600mj / cm 2 , UVA light intensity is 150mw / cm 2 , irradiation time 1.5min.
[0125] Example 3
[0126] 1. Preparation of acrylate polymer:
[0127] 58 parts by weight of dodecyl acrylate, 1.0 parts by weight of acrylic acid, 6 parts by weight of 4-hydroxybutyl acrylate, and 7 parts by weight of 2-hydroxy-3-phenoxypropyl methacrylate were stirred until uniform to obtain a mixed solution a;
[0128] Add 1.5 parts by weight of 1-hydroxycyclohexyl phenyl ketone to the mixed solution a, stir and mix evenly, and irradiate with ultraviolet light for polymerization at a stirring speed of 200 r / min to obtain an acrylate polymer, with an ultraviolet light intensity of UVA 25mw / cm 2 , cumulative energy UVA3500mj / cm 2 / 100g.
[0129] After testing, the weight average molecular weight of the obtained acrylic ester polymer is 300,000.
[0130] 2. Preparation of UV-curable adhesive composition:
[0131] 30 parts by weight of the above-prepared acrylic polymer, 15 parts by weight of NN-dimethyl(meth)acrylamide, 18 parts by weight of isooctyl acrylate, 6 parts by weight of vinyltrimethoxysilane, and 5 parts by weight of an ionic antistatic agent (FC-4400) were stirred evenly, and then 0.2 parts by weight of a photoinitiator OXE01 and 0.6 parts by weight of 907 were added, stirred until uniformly dissolved, defoamed, and stored away from light for later use.
[0132] 3. A method for preparing a polarizer, comprising the following steps:
[0133] S1. Unwind the PVA original film at the first unwinding position, and perform swelling, dyeing, bridging, stretching, washing, fixing and drying to obtain PVA polarizers; adhere PMMA and COP inner protective layers to the upper and lower surfaces of the PVA polarizers respectively through UV glue, the outer layer is the outer layer, and the PSA glue layer is the inner layer.
[0134] The water contact angle of the COP inner protective layer in contact with the adhesive layer is 45° after plasma treatment.
[0135] S2, unwinding the release film at the second unwinding station, coating the ultraviolet curing adhesive composition, laminating the inner COP inner protective layer after S1, and curing it through UV irradiation, with the irradiated surface being the release film surface.
[0136] S3, unwinding the PET protective film at the third unwinding position, attaching it to the outer inner protective layer passing through S2, and rewinding it to obtain a semi-finished polarizer.
[0137] S4, the upper semi-finished polarizer is unwound on the cutting line, and is cut and edge-grinded to obtain a finished polarizer sheet.
[0138] The preparation method of the upper polarizer, wherein the UV curing in S2 uses a high pressure mercury lamp UVA curing energy of 3000mj / cm 2 , UVA light intensity is 190mw / cm 2 , irradiation time 3min.
[0139] Example 4
[0140] 1. Preparation of acrylate polymer:
[0141] 50 parts by weight of dodecyl acrylate, 1.5 parts by weight of acrylic acid, 8 parts by weight of 2-hydroxyethyl acrylate, and 25 parts by weight of 2-hydroxy-3-phenoxypropyl methacrylate were stirred until uniform to obtain a mixed solution a;
[0142] 1.8 parts by weight of 1-hydroxycyclohexyl phenyl ketone was added to the mixed solution a, and the mixture was stirred and mixed evenly. The stirring speed was 200 r / min, and the mixture was irradiated with ultraviolet light for polymerization to obtain an acrylate polymer. The ultraviolet light intensity was UVA 50 mw / cm 2 , cumulative energy UVA3200mj / cm 2 / 100g.
[0143] After testing, the weight average molecular weight of the obtained acrylic ester polymer was 150,000.
[0144] 2. Preparation of UV-curable adhesive composition:
[0145] 38 parts by weight of the above-prepared acrylic polymer, 25 parts by weight of NN-dimethyl(meth)acrylamide, 15 parts by weight of isooctyl acrylate, 7 parts by weight of vinyltrimethoxysilane, and 2 parts by weight of an ionic antistatic agent (FC-4400) were stirred evenly, and then 0.12 parts by weight of a photoinitiator OXE01 and 0.6 parts by weight of 907 were added, stirred until uniformly dissolved, defoamed, and stored away from light for later use.
[0146] 3. A method for preparing a polarizer, comprising the following steps:
[0147] S1. Unwind the PVA original film at the first unwinding position, and perform swelling, dyeing, bridging, stretching, washing, fixing and drying to obtain PVA polarizers; adhere PMMA and PMMA inner protective layers to the upper and lower surfaces of the PVA polarizers respectively by UV glue, the outer layer is the outer layer, and the PSA adhesive layer is the inner layer.
[0148] The water contact angle of the PMMAinner protective layer in contact with the adhesive layer is 48° after corona treatment.
[0149] S2, unwinding the release film at the second unwinding station, coating the ultraviolet curing adhesive composition, laminating the inner PMMA inner protective layer after S1, and curing it through UV irradiation, with the irradiated surface being the release film surface.
[0150] S3, unwinding the PET protective film at the third unwinding position, attaching it to the outer inner protective layer passing through S2, and rewinding it to obtain a semi-finished polarizer.
[0151] S4, the upper semi-finished polarizer is unwound on the cutting line, and is cut and edge-grinded to obtain a finished polarizer sheet.
[0152] The preparation method of the upper polarizer, wherein the UV curing in S2 uses a high pressure mercury lamp UVA curing energy of 2000mj / cm 2 , UVA light intensity is 130mw / cm 2 , irradiation time 1min.
[0153] Comparative Example 1
[0154] This comparative example is a non-acidic adhesive for an existing ITO film, and its specific preparation method is as follows:
[0155] 15 parts of methyl acrylate, 20 parts of lauryl methacrylate, 18 parts of hydroxybutyl acrylate, 2 parts of acrylamide, 0.3 parts of azobisisobutyronitrile, 39 parts of ethyl acetate and 5.7 parts of acetone were added to the reactor in percentage by mass, nitrogen was passed through for 0.5 h to replace the air in the reactor, the stirrer was started and the temperature was gradually raised to 65°C within 40-50 min, and then maintained at this temperature for 18 h, and then cooled to obtain an acid-free high-adhesion acrylic adhesive.
[0156] Comparative Example 2
[0157] This comparative example is a comparative example of Example 3, except that the molecular weight of the acrylic acid ester polymer is higher than 300,000. The specific preparation process is as follows:
[0158] 1. Preparation of acrylate polymer:
[0159] 58 parts by weight of hexadecyl acrylate, 1.0 parts by weight of acrylic acid, 6 parts by weight of 4-hydroxybutyl acrylate, and 7 parts by weight of 2-hydroxy-3-phenoxypropyl methacrylate were stirred until uniform to obtain a mixed solution a;
[0160] Add 1.0 parts by weight of 1-hydroxycyclohexyl phenyl ketone to the mixed solution a, stir and mix evenly, and irradiate with ultraviolet light for polymerization at a stirring speed of 200 r / min to obtain an acrylate polymer, with an ultraviolet light intensity of UVA 25mw / cm 2 , cumulative energy UVA3500mj / cm 2 / 100g.
[0161] After testing, the weight average molecular weight of the obtained acrylic ester polymer was 380,000.
[0162] 2. Preparation of UV-curable adhesive composition: same as Example 3.
[0163] 3. A method for preparing a polarizer, same as in Example 3.
[0164] Comparative Example 3
[0165] This comparative example is a comparative example of Example 3, except that the molecular weight of the acrylic acid ester polymer is less than 100,000. The specific preparation process is as follows:
[0166] 1. Preparation of acrylate polymer:
[0167] 58 parts by weight of butyl acrylate, 1.0 parts by weight of acrylic acid, 6 parts by weight of 4-hydroxybutyl acrylate, and 7 parts by weight of 2-hydroxy-3-phenoxypropyl methacrylate were stirred until uniform to obtain a mixed solution a;
[0168] Add 2.0 parts by weight of 1-hydroxycyclohexyl phenyl ketone to the mixed solution a, stir and mix evenly, and irradiate with ultraviolet light for polymerization at a stirring speed of 200 r / min to obtain an acrylate polymer, with an ultraviolet light intensity of UVA 25mw / cm 2 , cumulative energy UVA3500mj / cm 2 / 100g.
[0169] After testing, the weight average molecular weight of the obtained acrylic ester polymer is 80,000.
[0170] 2. Preparation of UV-curable adhesive composition: same as Example 3.
[0171] 3. A method for preparing a polarizer, same as in Example 3.
[0172] Comparative Example 4
[0173] This comparative example is a comparative example of Example 3, except that the raw material for preparing the acrylate polymer does not use an aromatic ring-containing (meth)acrylate component.
[0174] The specific preparation process is as follows:
[0175] 1. Preparation of acrylate polymer:
[0176] 58 parts by weight of dodecyl acrylate, 1.0 parts by weight of acrylic acid, and 6 parts by weight of 4-hydroxybutyl acrylate were stirred until uniform to obtain a mixed solution a;
[0177] Add 1.5 parts by weight of 1-hydroxycyclohexyl phenyl ketone to the mixed solution a, stir and mix evenly, and irradiate with ultraviolet light for polymerization at a stirring speed of 200 r / min to obtain an acrylate polymer, with an ultraviolet light intensity of UVA 25mw / cm 2 , cumulative energy UVA3500mj / cm 2 / 100g.
[0178] After testing, the weight average molecular weight of the obtained acrylic ester polymer was 280,000.
[0179] 2. Preparation of UV-curable adhesive composition: same as Example 3.
[0180] 3. A method for preparing a polarizer, same as in Example 3.
[0181] Comparative Example 5
[0182] This comparative example is a comparative example of Example 3, except that when preparing the acrylate polymer, the amount of the raw material acrylic acid exceeds the specified range.
[0183] The specific preparation process is as follows:
[0184] 1. Preparation of acrylate polymer:
[0185] 58 parts by weight of dodecyl acrylate, 3.0 parts by weight of acrylic acid, 6 parts by weight of 4-hydroxybutyl acrylate, and 7 parts by weight of 2-hydroxy-3-phenoxypropyl methacrylate were stirred until uniform to obtain a mixed solution a;
[0186] Add 1.5 parts by weight of 1-hydroxycyclohexyl phenyl ketone to the mixed solution a, stir and mix evenly, and irradiate with ultraviolet light for polymerization at a stirring speed of 200 r / min to obtain an acrylate polymer, with an ultraviolet light intensity of UVA 25mw / cm 2 , cumulative energy UVA3500mj / cm 2 / 100g.
[0187] After testing, the weight average molecular weight of the obtained acrylic ester polymer is 300,000.
[0188] 2. Preparation of UV-curable adhesive composition: same as Example 3.
[0189] 3. A method for preparing a polarizer, same as in Example 3.
[0190] Comparative Example 6
[0191] This comparative example is a comparative example of Example 3, except that when the UV-curable adhesive composition is prepared, the amount of the raw material acrylate polymer is lower than the specified range.
[0192] The specific preparation process is as follows:
[0193] 1. Preparation of acrylic acid ester polymer: same as Example 3.
[0194] After testing, the weight average molecular weight of the obtained acrylic ester polymer is 300,000.
[0195] 2. Preparation of UV-curable adhesive composition:
[0196] 18 parts by weight of the above-prepared acrylic acid ester polymer, 15 parts by weight of NN-dimethyl (meth) acrylamide, 18 parts by weight of isooctyl acrylate, 6 parts by weight of vinyl trimethoxy silane, and 5 parts by weight of an ionic antistatic agent (FC-4400) were stirred evenly, and then 0.2 parts by weight of a photoinitiator OXE01 and 0.6 parts by weight of 907 were added, stirred until uniformly dissolved, defoamed, and stored away from light for later use.
[0197] 3. A method for preparing a polarizer, same as in Example 3.
[0198] Comparative Example 7
[0199] This comparative example is a comparative example of Example 3, except that when the UV-curable adhesive composition is prepared, the amount of the raw material acrylate polymer used is higher than the specified range.
[0200] The specific preparation process is as follows:
[0201] 1. Preparation of acrylic acid ester polymer: same as Example 3.
[0202] After testing, the weight average molecular weight of the obtained acrylic ester polymer is 300,000.
[0203] 2. Preparation of UV-curable adhesive composition:
[0204] 45 parts by weight of the above-prepared acrylic polymer, 15 parts by weight of NN-dimethyl(meth)acrylamide, 18 parts by weight of isooctyl acrylate, 6 parts by weight of vinyltrimethoxysilane, and 5 parts by weight of an ionic antistatic agent (FC-4400) were stirred evenly, and then 0.2 parts by weight of a photoinitiator OXE01 and 0.6 parts by weight of 907 were added, stirred until uniformly dissolved, defoamed, and stored away from light for later use.
[0205] 3. A method for preparing a polarizer, same as in Example 3.
[0206] Comparative Example 8
[0207] This comparative example is a comparative example of Example 3, and the difference is that when the UV-curable adhesive composition is prepared, the ratio between the photoinitiator OXE01 and the photoinitiator 907 exceeds the specified range, and the amount of the photoinitiator 907 used is too large.
[0208] The specific preparation process is as follows:
[0209] 1. Preparation of acrylic acid ester polymer: same as Example 3.
[0210] After testing, the weight average molecular weight of the obtained acrylic ester polymer is 300,000.
[0211] 2. Preparation of UV-curable adhesive composition:
[0212] 30 parts by weight of the above-prepared acrylic polymer, 15 parts by weight of NN-dimethyl(meth)acrylamide, 18 parts by weight of isooctyl acrylate, 6 parts by weight of vinyltrimethoxysilane, and 5 parts by weight of an ionic antistatic agent (FC-4400) were stirred evenly, and then 0.2 parts by weight of a photoinitiator OXE01 and 1.2 parts by weight of 907 were added, stirred until uniformly dissolved, defoamed, and stored away from light for later use.
[0213] 3. A method for preparing a polarizer, same as in Example 3.
[0214] Comparative Example 9
[0215] This comparative example is a comparative example of Example 3, and the difference is that in the (meth)acrylate alkyl ester used in the UV-curable adhesive composition, the carbon number of the alkyl group exceeds the limited range of 4 to 8.
[0216] The specific preparation process is as follows:
[0217] 1. Preparation of acrylic acid ester polymer: same as Example 3.
[0218] After testing, the weight average molecular weight of the obtained acrylic ester polymer is 300,000.
[0219] 2. Preparation of UV-curable adhesive composition:
[0220] 30 parts by weight of the above-prepared acrylic acid ester polymer, 15 parts by weight of NN-dimethyl (meth) acrylamide, 42 parts by weight of octadecyl acrylate, 6 parts by weight of vinyl trimethoxy silane, and 5 parts by weight of an ionic antistatic agent (FC-4400) were stirred evenly, and then 0.2 parts by weight of a photoinitiator OXE01 and 0.6 parts by weight of 907 were added, stirred until uniformly dissolved, defoamed, and stored away from light for later use.
[0221] 3. A method for preparing a polarizer, same as in Example 3.
[0222] Comparative Example 10
[0223] This comparative example is a comparative example of Example 3, and the difference is that: during the preparation process of the polarizer, the contact process and contact angle between the adhesive layer and the inner protective layer are different.
[0224] The specific preparation process is as follows:
[0225] 1. Preparation of acrylic acid ester polymer: same as Example 3.
[0226] After testing, the weight average molecular weight of the obtained acrylic ester polymer is 300,000.
[0227] 2. Preparation of UV-curable adhesive composition: same as Example 3.
[0228] 3. A method for preparing a polarizer is basically the same as that of Example 3, except that the side of the COP inner protective layer in contact with the adhesive layer is not plasma treated, and the water contact angle is 80°.
[0229] The polarizers prepared in Examples 1 to 4 and Comparative Examples 1 to 10 were subjected to performance tests. The performance test items and test methods are as follows:
[0230] Peeling force test: Take a sample with a width of 25mm and a length of about 150mm, prepare an ITO glass with a flat surface, wipe it clean with a dust-free cloth lightly dipped in ethanol, let it stand for 30 minutes, stick the sample on the glass, use a 2kg pressure roller to roll the prepared sample back and forth three times at a speed of 10±0.5mm / s, let it stand for 24 hours at a temperature of 23±2℃ and a relative humidity of 50±5%, peel it 180° at a speed of 300mm / min, record the value, and measure the sample three times in parallel.
[0231] Durability test: high temperature 80℃, high temperature and humidity 60℃, 90% RH, cold -35℃, hot and cold shock -35~80℃. Put the polarizer on the ITO glass and put it into the above conditions for testing.
[0232] Appearance: Visually inspect for any curling defects.
[0233] Table 1 Performance test table of polarizer adhesives prepared in Examples and Comparative Examples
[0234]
[0235]
[0236] It can be seen from the data in the table that the UV-curable adhesive composition of the present application does not contain volatile matter, is environmentally friendly and reduces carbon emissions. The UV-curable adhesive composition of the present application has good durability to ITO, and the polarizer will not produce warping defects.
[0237] Comparative Example 1 The prior art acid-free pressure-sensitive adhesive is a solvent-based heat-curing pressure-sensitive adhesive, which has the problems of poor reworkability and difficulty in tearing.
[0238] In comparative example 2, the molecular weight of the acrylic polymer is greater than 300,000, the Tg of the obtained adhesive is too low, the peel strength at room temperature increases too fast in 30 days, there is a risk of difficulty in tearing after heavy work, and there are bubbles and poor floating in the durability test.
[0239] In Comparative Example 3, the molecular weight of the acrylic polymer is too low, the Tg of the obtained adhesive is too high, there is residual adhesive in the peel strength test, there are bubbles and poor floating in the durability test, and the polarizer has poor curling due to excessive shrinkage.
[0240] The acrylic polymer of Comparative Example 4 did not contain aromatic rings during the preparation process, and had bubbles and poor floating in the durability test.
[0241] In Comparative Example 5, the acrylic acid content of the acrylic acid ester polymer exceeded the range, the Tg of the resulting adhesive was too high, the peel strength test was too high, and the durability test had bubbles and poor floating.
[0242] In comparative example 6, too little acrylate component was added, the Tg of the obtained adhesive was too high, the initial peel force was low, bubbles and poor floating were found in the durability test, and the polarizer had poor curling due to excessive shrinkage.
[0243] In comparative example 7, too much acrylate component was added, the Tg of the obtained adhesive was too low, the initial peeling force was too high and there was residual glue, and the peeling force after 30 days at room temperature was too high, there was residual glue, and it was difficult to tear.
[0244] In the adhesive composition of Comparative Example 8, the ratio of OXE01:907 is 1:6, the deep curing is uneven, there is residual adhesive in the peeling force, and there are bubbles and floating in the weather resistance test.
[0245] Comparative Example 9 uses octadecyl acrylate, and the number of carbon atoms of the alkyl group exceeds the specified range, resulting in the adhesive Tg being too low, the peel strength test being too high and having residual adhesive, and the peel strength at room temperature after 30 days being too high, with residual adhesive and difficulty in tearing.
[0246] The film material bonded with the adhesive in Comparative Example 10 was not plasma treated, and the water contact angle was 80°. The peeling force test showed that the film material was debonded, and the weather resistance test showed that the film material floated.
[0247] It should be emphasized that the above are only preferred embodiments of the present invention and do not limit the present invention in any form. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. An acrylic acid ester polymer, characterized in that: The main structure of the acrylic ester polymer adopts (meth) alkyl acrylate, and the main chain and side chain of the acrylic ester polymer do not contain unsaturated bond functional groups; the weight average molecular weight of the acrylic ester polymer is 100,000 to 300,000.
2. The acrylate polymer according to claim 1, characterized in that: The raw materials for preparing the acrylic ester polymer include 50-65 parts by weight of (meth) alkyl acrylate, 0.01-2 parts by weight of carboxyl-containing monomer, 3-12 parts by weight of hydroxyl-containing monomer, 7-25 parts by weight of (meth) acrylate containing aromatic ring, and 0.5-3 parts by weight of photoinitiator; the raw materials are mixed and polymerized under ultraviolet light to generate the acrylic ester polymer.
3. The acrylic acid ester polymer according to claim 3, characterized in that: The (meth)acrylic acid alkyl ester is linear or branched, and the number of carbon atoms in the alkyl group is 1-18; The carboxyl group-containing monomer is selected from any one of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, carboxypentyl acrylate, carboxypentyl methacrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid; The hydroxyl-containing monomer is selected from 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl acrylate, 6-hydroxyhexyl methacrylate, 8-hydroxyoctyl acrylate, 8-hydroxyoctyl methacrylate, 8-hydroxyoctyl acrylate, 8-hydroxyoctyl methacrylate, 6-hydroxyhexyl acrylate, 6-hydroxyhexyl methacrylate, 2-hydroxyethylene glycol. Acrylate, 2-hydroxyethylene glycol methacrylate, 2-hydroxypropylene glycol acrylate, 2-hydroxypropylene glycol methacrylate, 10-hydroxydecyl acrylate, 10-hydroxydecyl methacrylate, 12-hydroxylauryl acrylate, 12-hydroxylauryl methacrylate; more preferably any one of 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl acrylate, and 6-hydroxyhexyl methacrylate; The aromatic ring-containing (meth)acrylate is selected from benzyl acrylate, benzyl methacrylate, phenyl acrylate, phenyl methacrylate, o-phenylphenol acrylate, methyl o-phenylphenol acrylate, phenoxy acrylate, phenoxy methacrylate, phenoxyethyl acrylate, phenoxyethyl methacrylate, phenoxypropyl acrylate, phenoxypropyl methacrylate, phenoxydiethylene glycol acrylate, phenoxydiethylene glycol methacrylate, ethylene oxide-modified nonylphenol acrylate, ethylene oxide-modified nonylphenyl Any one of phenol methacrylate, 2-hydroxy-3-phenoxypropyl acrylate, 2-hydroxy-3-phenoxypropyl methacrylate, methoxybenzyl acrylate, methoxybenzyl methacrylate, toluene acrylate, toluene methacrylate, 2-naphthylethyl acrylate, 2-naphthylethyl methacrylate, 2-naphthyloxyethyl acrylate, 2-(4-methoxy-1-naphthyloxy)ethyl acrylate, 2-(4-methoxy-1-naphthyloxy)ethyl methacrylate, biphenyl acrylate, and biphenyl methacrylate; The photoinitiator is selected from any one of benzoin diethyl ether, 1-hydroxycyclohexyl phenyl ketone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, 2-methyl-4-methylthio-2-morpholinophenylpropiotone, and 2-hydroxy-2-methyl-1-phenylpropiotone, or a mixture thereof.
4. A UV-curable adhesive composition, characterized in that: The invention comprises 20 to 40 parts by weight of the acrylic acid ester polymer according to any one of claims 1 to 3, 15 to 35 parts by weight of an amide group-containing monomer, 13 to 40 parts by weight of an alkyl (meth)acrylate, 5 to 8 parts by weight of a silane compound, 1 to 5 parts by weight of an antistatic agent and 0.4 to 1.0 parts by weight of a photoinitiator.
5. The UV-curable adhesive composition according to claim 4, characterized in that: The amide group-containing monomer refers to a compound containing an amide group in its structure and containing polymerizable unsaturated double bonds such as acryloyl, methacryloyl, and vinyl groups; The (meth)acrylic acid alkyl ester is a linear or branched alkyl acrylate; The silane compound is a reactive silane compound containing silicon atoms; The antistatic agent is any one or two of conductive polymers, ionic compounds, conductive particles, organic silicon compounds, and nano-scale carbon nanotubes; The photoinitiator is selected to have an absorption wavelength band of 300-400nm for active energy rays.
6. The UV-curable adhesive composition according to claim 5, characterized in that: The amide group-containing monomer can be selected from any one of (meth)acrylamide, NN-dimethyl (meth)acrylamide, NN-diethyl (meth)acrylamide, N-isopropyl acrylamide, N-methyl (meth)acrylamide, N-butyl (meth)acrylamide, N-hexyl (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, N-propyl (meth)acrylamide, aminomethyl (meth)acrylamide, aminoethyl (meth)acrylamide, N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylpyrrolidone, and N-vinyl-Ɛ-caprolactam; The carbon number of the alkyl group in the (meth)acrylic acid alkyl ester is 4 to 8; The silane compound is selected from any one of 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloxydecyltrimethoxysilane, 10-acryloxydecyltrimethoxysilane, 10-methacryloxydecyltriethoxysilane, and 10-methacryloxydecylethoxysilane; The antistatic agent is selected from one or a mixture of two or more conductive polymers such as polyaniline and polythiophene; an appropriate amount of dopant may be added to the conductive polymer; The photoinitiator is a compound of OXE01+907, and the compounding ratio of the two is 1:(3~5).
7. The UV-curable adhesive composition according to any one of claims 4 to 6, characterized in that: The viscosity η of the adhesive composition at 25° C. is in the range of 2000 cps≤η≤5000 cps; the glass transition temperature T of the adhesive composition is g :-60℃≤T g ≤-30°C; the gel fraction of the adhesive composition is 75%~85%.
8. A polarizer, characterized in that: The invention comprises a PVA layer (1), an outer protective layer (3) and an inner protective layer (4) which are bonded to the upper and lower surfaces of the PVA layer (1) via a UV adhesive (2), a release film (7) being adhered to the outer side of the inner protective layer (4) via an adhesive layer (6), and a protective film (5) being arranged on the outer side of the outer protective layer (3); the adhesive layer (6) is a UV-curable adhesive composition according to any one of claims 4 to 7.
9. The polarizer according to claim 8, characterized in that: The thickness of the adhesive layer (6) is 10-30 μm, and the surface resistance is 9.9×10 11 Ω / □ or less.
10. The polarizer according to claim 8, characterized in that: When the inner protective layer (4) is a hydrophilic film material, the water contact angle when it contacts the adhesive composition is ≤35°; when the inner protective layer (4) is a hydrophobic film material, the water contact angle when it contacts the adhesive composition is ≤48°.
Citation Information
Cited By
Ultraviolet curing adhesive composition and polaroid
CN120829727A